Validating bachelorhood : audience, patriarchy and Charles Brockden Brown's editorship of the Monthly Magazine and American Review /: audience, patriarchy and Charles Brockden Brown's editorship of the Monthly Magazine and American Review. (2016) - Slawinski, Scott
No abstract available